1996
DOI: 10.1063/1.117237
|View full text |Cite
|
Sign up to set email alerts
|

Schottky barriers and contact resistances on p-type GaN

Abstract: We measured the Schottky barrier heights and specific contact resistivities of four different metals on p-type GaN. The Schottky barrier heights of Pt, Ni, Au, and Ti were obtained from the current-voltage characteristics to be 0.50, 0.50, 0.57, and 0.65 eV, respectively. The specific contact resistivities were 0.013, 0.015, 0.026, and 0.035 Ω⋅cm2, respectively. Our experimental results proved that the Schottky barrier heights and specific contact resistivities decrease with increase in metal work function as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
3
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(107 citation statements)
references
References 9 publications
5
98
3
1
Order By: Relevance
“…Kurtin et al [32] suggested that the Schottky barrier height on GaN should depend directly on the work function or electronegativity difference between the metal electrode and GaN. Foresi and Moustakas [33] observed this direct correlation experimentally, while Guo et al [34] and Mori et al [35] observed only a weak dependence of the Schottky barrier height on the metal work function for n-type GaN and p-type GaN, respectively. The 1998 review of metal-GaN contact technology by Liu and Lau [19] reported that, for a variety of contact metals with both low and high work functions, Schottky barrier heights at the metal-GaN interface varied with metal work function, within the experimental scatter.…”
Section: Introductionmentioning
confidence: 84%
“…Kurtin et al [32] suggested that the Schottky barrier height on GaN should depend directly on the work function or electronegativity difference between the metal electrode and GaN. Foresi and Moustakas [33] observed this direct correlation experimentally, while Guo et al [34] and Mori et al [35] observed only a weak dependence of the Schottky barrier height on the metal work function for n-type GaN and p-type GaN, respectively. The 1998 review of metal-GaN contact technology by Liu and Lau [19] reported that, for a variety of contact metals with both low and high work functions, Schottky barrier heights at the metal-GaN interface varied with metal work function, within the experimental scatter.…”
Section: Introductionmentioning
confidence: 84%
“…[7][8][9][21][22][23][24] The activation energy of the Mg acceptor level is taken at ͑ E t -E v )ϭ0.16 eV. The Schottky barrier height q b is taken 0.70 eV.…”
Section: A Schottky Gan:mg Junction Under Room Temperature Zero-biamentioning
confidence: 99%
“…11, contact resistivity rapidly decreases as increase in the defect density, and it also decreases when the qφ decreases. In order to obtain the defect density in the p-GaN films, the qφ was measured by using the devised I-V method which utilizes large-area contacts and reverse-biased I-V characteristics, [39] and the measured qφ was 0.36 eV. From the measured Fig.…”
Section: Influence Of Deep Level Defects On the Carrier Transportmentioning
confidence: 99%